Socio-cultural resource of management strategy of modern China - L. V. Filindash (Вестник университета)
The article studies main socio-cultural resources that ensure the success of the management strategy of modern China. The Law “On Public Service” is considered as an important legal resource regulating the activities of public personnel. Since the social stability of the Chinese society is explained by the multiparty political system of the country with the leading role of the Communist Party of China, the article presents a table compiled by the author about the parties, including the logo, information about the leaders and their education, data on the degree of influence of each party in society and its establishment time. The possibility of consultations with the participation of all officially operating parties guarantees the Communist Party of China the adoption of a theoretically grounded plan for ongoing reforms implementation, which is interpreted as an important managerial resource along with personnel policy. The socio-cultural vector of the management strategy is interpreted in the discourse of the building socialism theory with Chinese specifics, which implies the living standards improvement with industries development that provide vital human needs and socially important innovation directions in science and economy. The author concludes that the management strategy resources have a multi-vector character, which is manifested in economic and cultural, scientific and technological, political and ideological spheres.